2021
DOI: 10.31234/osf.io/7uh6f
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Scaring away anxiety: Therapeutic avenues for horror fiction to enhance treatment for anxiety symptoms

Abstract: From scary stories to horror films and haunted houses, the horror genre is wildly popular. Although horror aims to elicit fear and anxiety in its audience, many people with anxiety are horror fans and some report using horror to cope with their anxiety. In this article, we provide a theoretical rationale for why people with anxiety might find relief in horror films. First, we discuss aspects of horror that could make it particularly alluring to people with anxiety and how some features of horror films have the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 67 publications
0
27
0
Order By: Relevance
“…The lifestyle effects of being morbidly curious, and the extent to which morbid curiosity can change over time, will be interesting to explore in future studies. Understanding individual differences in morbid curiosity could be useful in a variety of fields, including tourism (e.g., dark tourism), media (e.g., news and movie preferences), clinical psychology (e.g., see Scrivner & Christensen, 2021), criminology (e.g., in relation to psychopathy), and others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lifestyle effects of being morbidly curious, and the extent to which morbid curiosity can change over time, will be interesting to explore in future studies. Understanding individual differences in morbid curiosity could be useful in a variety of fields, including tourism (e.g., dark tourism), media (e.g., news and movie preferences), clinical psychology (e.g., see Scrivner & Christensen, 2021), criminology (e.g., in relation to psychopathy), and others.…”
Section: Discussionmentioning
confidence: 99%
“…This is surprising given that individual differences in morbid curiosity likely exist. Moreover, research on morbid curiosity and related topics has become increasingly more common (e.g., Andersen et al, 2020;Clasen, 2012;Clasen, 2017;Clasen et al, 2019;Harrison & Frederick, 2020;Kerr, 2015;Kerr et al, 2019;Martin, 2019;Niehoff & Oosterwijk, 2020;Oosterwijk, 2017;Oosterwijk et al, 2020;Robinson et al, 2014;Scrivner 202;Scrivner & Christensen, 2021;Scrivner et al, 2020;Stone & Sharpley, 2008;Vicary & Fraley, 2010;Wabnegger et al, 2021). This boom in research -largely in the field of psychology -on morbid curiosity and related psychological and behavioral phenomena implies that the construct is interesting, relevant, and in need of theoretical clarification and an appropriate assessment tool.…”
Section: Morbid Curiositymentioning
confidence: 99%
“…Like risky or thrilling play (Sandseter & Kennair, 2011), engaging in recreational fear may be a useful way to learn how to respond to dangerous phenomena (Miller et al forthcoming;Morin et al, 2019;Scrivner, 2021a). For instance, horror fiction offers an opportunity to practice emotion regulation strategies that could be useful for related situations in the real world (Scrivner & Christensen, 2021). In support of this idea, one study found that horror fans appeared to have greater psychological resilience during the early months of the COVID-19 pandemic than non-horror fans (Scrivner et al, 2021).…”
Section: Play and The Threat Simulation Account Of Horrormentioning
confidence: 98%
“…Anecdotal evidence suggests that some individuals may find solace from their anxiety and depression through using horror entertainment (e.g., Grisafi 2016; Turner 2017), which aligns well with items on the Dark Coper scale. Correspondingly, Scrivner and Christensen (2021) have argued that horror possesses particular cognitive attractors for individuals with elevated anxiety and may hold therapeutic value in the form of increased emotion regulation and generalized psychological resilience (see also Sandseter & Kennair, 2011;.…”
Section: 3mentioning
confidence: 99%
“…This observation is as close as the researcher came to explaining how anxiety reduction could be achieved, to enable coping. Somewhat similar is the view of Srivner and Christensen (2021), who claimed that some of the horror movies feature decreased anxiety, while concurrently building resilience skills, including the cognitive ones that enable coping with fear and anxiety. Lincoln (1998) too, offered a brilliant rationale behind the popularity of such movies: they indicated that a cataclysmic change resulted in weak people being exalted and mighty ones being humbled (cited in Hamonic, 2017).…”
Section: Binge-watching and Panic-buying As Juncture-inducedmentioning
confidence: 65%